KEMANDIRIAN EKONOMI; MEMBENTUK MASYARAKAT DALAM PENGEMBANGAN BUDIDAYA IKAN BUBARA - Julisa Aprilia Kaluku; Lisnawaty W Badu; Janwar Hippy (Journal of Community Services on Multidisciplinary Sciences, 2025)
Community empowerment through bubara fish cultivation is one of the efforts to empower the village community through the maintenance and development of bubara fish, so that it can give results in improving the economic condition of the community. Therefore, this effort should be carried out with the principles of community-based empowerment and development in improving the economy of the local community. The role of the community is urgently needed as the main actor in all stages of planning, implementation, monitoring and evaluation of activities. However, there is also a need for support and cooperation from other stakeholders such as related agencies of local governments, village governments and the private sector which have greater resources in terms of finance, partnerships, information, knowledge, and technology.